(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the key socio-psychological factors influencing the formation of the modern youth’s worldview. The research highlights the impact of digital technologies, globalization, and shifts in value systems on the consciousness of the younger generation. Furthermore, the article pays special attention to issues such as the pursuit of individualism, cognitive characteristics, and the processes of socialization in a virtual environment. The findings serve to improve pedagogical and psychological approaches in working with youth.